Conceptual framework: Gender, climate change, and nutrition integration initiative - Bryan, Elizabeth; Theis, Sophie; Choufani, Jowel; De Pinto, Alessandro; Meinzen-Dick, Ruth S.; Ringler, Claudia (International Food Policy Research Institute, 2017)
To guide these activities, IFPRI has developed a conceptual framework that integrates climate resilience, gender, and nutrition, with input from USAID and its implementing partners. The purpose of the framework is to identify and describe key elements of resilience, while highlighting the linkages with gender and nutrition. The goal of developing this framework is to provide stakeholders from different disciplines and backgrounds with a common point of reference for understanding these complex issues and their interlinkages. The framework can also be used to identify research and evidence gaps, and to highlight entry points for programs and projects that aim to influence outcomes, such as resilience, nutrition, or women’s empowerment.